Evaluation of Mast-ID 15 system for identification of fresh clinical isolates of Enterobacteriaceae and Acinetobacter. - Shakespeare, A. P. (1992)
AIMS: To assess the accuracy of the Mast-ID 15 system compared with API 20 E for the identification of stock and fresh clinical strains of Enterobacteriaceae and Acinetobacter spp; to compare the accuracy of 19 pin and 36 pin multipoint inoculator heads. METHODS: One hundred frozen stock cultures of Enterobacteriaceae and Acinetobacter spp which had previously been identified by the API 20E were classified by the Mast-ID using 19 and 36 pin multipoint inoculator heads. Reproducibility was determined by testing 36 randomly selected organisms in duplicate. Four hundred and sixty nine consecutive fresh clinical isolates of Enterobacteriaceae and Acinetobacter spp were identified by the Mast-ID using a 36 pin multipoint inoculator and by the API 20E. Reproducibility for the fresh isolates was determined by testing 96 randomly selected strains in duplicate. RESULTS: The Mast-ID 15 identified 82% and 85% of frozen strains to species level and reproducibility was 80% and 86% using 19 and 36 pin inoculator heads, respectively. Of the 469 fresh clinical isolates, the Mast-ID identified 70% of strains to species level; 19% were not identified and 11% were identified incorrectly by comparison with the API 20E. The Mast-ID achieved a reproducibility level of 80% with the fresh clinical isolates. CONCLUSIONS: The use of a 36 pin multipoint inoculator head in preference to the standard 19 pin head for the Mast-ID was advantageous as it allowed greater numbers of strains to be identified at a reduced cost. Unfortunately, in our hands, the Mast-ID system was insufficiently accurate for routine use in the clinical laboratory. Modifications to some of the problematic tests may result in a sufficient increase in accuracy and reproducibility to make the system beneficial in the routine clinical laboratory.